2013
DOI: 10.1155/2013/673150
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Validation Study of Fluconazole by HPLC and UPLC with Forced Degradation Study

Abstract: The simplest stability indicating reversed phase Isocratic HPLC and UPLC methods has been developed and validated for the determination of fluconazole in bulk and solid pharmaceutical dosage form. A SunFire C18 (250 × 4.5 mm, 5 μm particle size) column has been used for HPLC and BEH C18 (100 × 2.1 mm, 1.7 μm particle size) column used for UPLC. The Mobile phase consisted of Methanol : Water (70 : 30) for HPLC and Methanol : Water (55 : 45 v/v) for UPLC. Isocratic flow was set at 1 mL/min and 0.30 mL/min, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Admitting the previously mentioned AOAC acceptance criteria, the developed method is not able to adequately determine the drugs after their degradation [40,42], except FL exposure at alkaline pH. It is suggested that the low percentage of recovery after the stress study is due to the high degradation of FL and CUR under the analyzed conditions, similar to that was observed in the studies conducted by Jebaliya et al [43], and Syed et al [44]. Thus, based on the results obtained, the proposed method is not suitable for the quantification of CUR and FL under conditions of photolysis, oxidative damage, and degradation in alkaline and acidophilic mediums.…”
Section: Stress Testmentioning
confidence: 70%
“…Admitting the previously mentioned AOAC acceptance criteria, the developed method is not able to adequately determine the drugs after their degradation [40,42], except FL exposure at alkaline pH. It is suggested that the low percentage of recovery after the stress study is due to the high degradation of FL and CUR under the analyzed conditions, similar to that was observed in the studies conducted by Jebaliya et al [43], and Syed et al [44]. Thus, based on the results obtained, the proposed method is not suitable for the quantification of CUR and FL under conditions of photolysis, oxidative damage, and degradation in alkaline and acidophilic mediums.…”
Section: Stress Testmentioning
confidence: 70%
“…Eight milliliters of phosphate buffered saline (pH 6.8) prepared from disodium hydrogen phosphate (Na 2 HPO 4 anhydrous) = 14.4 g sodium dihydrogen phosphate (KH 2 PO 4 anhydrous) = 2.4 g sodium chloride (NaCl) = 80.0 g, and potassium chloride (KCl) = 2.0 g, was kept in the receptor chamber, which was maintained at 32 ± 2 °C with the help of a warm water jacket and stirred at 410 to 430 rpm using the magnetic bead. The samples were autosampled at predetermined time intervals and quantified in parallel using high-performance liquid chromatography (HPLC) [ 22 ]. Diffusion of the fluconazole from the donor compartment to the receptor compartment through the mounted mucous membrane was determined by plotting the cumulative release pattern of the drug per unit of time and area.…”
Section: Methodsmentioning
confidence: 99%
“…It is widely used to treat fungal infections caused by cryptococci, candida and coccidia, and it is official in Indian Pharmacopoeia 1 . The most commonly used techniques for determining FLU in pharmaceutical dosage forms and biological fluid are the UV-Spectrophotometric [22][23] , HPLC [24][25][26][27] , UPLC 28 and LC-MS [29][30] .…”
Section: Introductionmentioning
confidence: 99%